Enabling Sustainability Through the Internet of Things: A Narrative Review of Global Applications and Challenges - Sucipto, Purwo Agus; Dewi, Ratna Kusuma (Indonesian Scientific Publication, 2025)
The Internet of Things (IoT) has emerged as a transformative framework with broad applications in healthcare, agriculture, energy, and urban systems. This review aims to synthesize current evidence on IoT adoption, assessing both its benefits and the challenges hindering large-scale implementation. Literature was systematically retrieved from major databases, including Scopus, Web of Science, PubMed, and Google Scholar, using targeted keywords and strict inclusion and exclusion criteria. Findings reveal consistent evidence of IoT’s contribution to efficiency and sustainability: precision agriculture improves yields and resource use, while smart energy systems reduce consumption in urban infrastructures. Comparative results demonstrate disparities between developed and developing countries, with advanced economies emphasizing integrated high-tech solutions and resource-limited settings prioritizing affordable, accessible innovations. The discussion highlights the critical role of systemic and policy factors, including regulatory support, infrastructural investment, and societal trust, in shaping adoption outcomes. Emerging technologies such as blockchain and machine learning show promise for addressing challenges of security and energy efficiency but require further empirical validation in real-world contexts. While current research supports IoT’s role in advancing sustainable development, significant gaps remain in understanding its long-term socio-economic impacts and scalability. The findings emphasize the urgency of policy interventions, inclusive strategies, and interdisciplinary research to fully realize IoT’s potential as a driver of sustainable and equitable global transformation.